2020
DOI: 10.1186/s11671-020-03349-2
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Resolution EDX, HAADF, and EELS Study of GaAs1-xBix Alloys

Abstract: The distribution of alloyed atoms in semiconductors often deviates from a random distribution which can have significant effects on the properties of the materials. In this study, scanning transmission electron microscopy techniques are employed to analyze the distribution of Bi in several distinctly MBE grown GaAs 1−x Bi x alloys. Statistical quantification of atomic-resolution HAADF images, as well as numerical simulations, are employed to interpret the contrast from Bi-containing columns at atomically abrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Our previous atomically-resolved STEM-EDX ordering parameter evaluation yielded a η = 0.07 value for a sample with 5.5 % Bi. 13,14 Although the ordering parameters for the present S1-S6 samples were not examined by EDX, one can expect them to be of the order of η ~ 0.1. Next, sample S6 is examined, which together with S1-S5, was used in the optical anisotropy analysis.…”
Section: B Atomic Orderingmentioning
confidence: 89%
See 2 more Smart Citations
“…Our previous atomically-resolved STEM-EDX ordering parameter evaluation yielded a η = 0.07 value for a sample with 5.5 % Bi. 13,14 Although the ordering parameters for the present S1-S6 samples were not examined by EDX, one can expect them to be of the order of η ~ 0.1. Next, sample S6 is examined, which together with S1-S5, was used in the optical anisotropy analysis.…”
Section: B Atomic Orderingmentioning
confidence: 89%
“…This typically leads to larger ordered domains, and a single subvariant ordering has also been confirmed in GaAsBi. 13,14 The ordering is never perfect and is quantified by the ordering parameter η. A partially ordered alloy AB1−xCx can be described as AB1−(x−η/2)Cx−η/2 and AB1−(x+η/2)Cx+η/2 monolayers on (1 ̅ 11) or (11 ̅ 1) planes, with a maximal value of ordering parameter ηmax= min[2x, 2(1−x)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the superficial area and the focused shape of electronic beam must be contemplated, which also affects the detection resolution. 65 In addition to these factors, higher peak to background ratio indicated that SACs could be identified by EDX.…”
Section: Characterization Techniques For Evidence Of Single Atoms In ...mentioning
confidence: 99%
“…Despite their high sensitivity, these measurements cannot be applied to probe small volumes, let alone the lattice position of individual dopants and their interactions at the local scale, as they lack the necessary spatial resolution. To image single dopant atoms within the lattice and quantify their concentration, scanning transmission electron microscopy (STEM) has been applied in combination with energy-dispersive X-ray spectroscopy (EDX) 13,14 . This correlated approach represents a breakthrough in the atomic-scale characterization of doped oxides, but it is limited to doping levels higher than a few at.%.…”
mentioning
confidence: 99%